Estimativa do consumo máximo de oxigênio a partir do teste de Carminatti (T-Car) em atletas de futebol e futsal - Ricardo D. Lucas; Alex F. Tomé; Juliano F. Silva; Naiandra Dittrich; Renan F. H. Nunes; Luiz G. A. Guglielmo; Paulo C. N. Salvador (Universidade Estadual do Oeste do Paraná, 2016)
The search for increasingly specific tests to evaluate athletes has been the subject of scientific studies in recent decades. Thus, the Carminatti's test running (T-CAR) was proposed in 2004 in order to assess aerobic fitness sport athletes with intermittent characteristics such as team sports. The main variable obtained in this field test is the peak velocity (PV) that represents the maximum aerobic speed. In turn, the maximum oxygen consumption (VO2max) is considered as the physiological index that best represents the power of aerobic metabolism. The possibility of the PV obtained by the T-CAR estimate VO2max was not analyzed in the literature. Thus, the aim of this study was to propose a mathematical equation to predict VO2max from the performance obtained in T-CAR. Forty five professional players from futsal and soccer of state of Santa Catarina took part of the study. Players were evaluated on two occasions one in laboratory (incremental test running in the treadmill), and in the field (intermittent incremental test T-CAR). Both tests were conducted until voluntary exhaustion. The test performed in the laboratory, the VO2max was obtained directly using a gas analyzer. The mean values found among the study participants was 59,1 ± 4,8 ml.kg-1.min-1 (VO2max) and 16.5 ± 0.9 km.h-1 for PV T-CAR. The linear regression analysis using the PV obtained in T-CAR resulted in the following predicting equation: VO2max = 16,6 + 2,59*PV (r=0,46; p=0,001) and a standard error of estimate 4,3 ml.kg-1.min-1. Thus, it is concluded that the peak velocity obtained in T-CAR can be used, but with some caution, as VO2max predictor in soccer and futsal athletes.